Pelatihan Penghayatan Al-Qur’an untuk Meningkatkan Kebermaknaan Hidup Bagi Mahasiswa dengan Orang Tua Bercerai - Pihasniwati Pihasniwati (Jurnal Psikologi Integratif, 2017)
The aim of this study is for examining the effectivity of Qur’anic Comprehension Training to the level of the meaning of life in students with divorced parents. The subjects are consist of six people, four women and two men, students of UIN Yogyakarta. Analysis method using Wilcoxon with SPSS 20.0 computer program. To measure the meaning of life using measurement scale, interview and observation. Result of this study is there is an increasing in the meaning of life in subjects after the intervention. Coefficient of difference (Z) between pretest-posttest is -2.207, with significance level (p) 0.027 (p<0.5) in individual analysis and group analysis. Thus, Qur’anic comprehension training proved can increase the meaning of life in students with divorced parents.